Respostas

2014-06-02T16:49:32-03:00
A)x²+6x+5=0   onde a=1   b=6   c=5
  
Δ=b²-4.a.c
Δ=6²-4.1.5
Δ=36-20
Δ=16   ⇔raiz quadrada de 16 é 4

x'=-6+4    -2
   ¨¨¨¨¨¨¨¨ =¨¨¨¨¨¨ = -1
       2.1     2


x"=-6-4     -10
    ¨¨¨¨¨¨¨¨=¨¨¨¨¨¨¨¨= -5                                  S:(-1, -5)
      2.1       2



b)x²-2x+1=0      onde     a=1      b=-2   c=1

Δ=b²-4.a.c
Δ=(-2)²-4.1.1
Δ=4-4
Δ=0  ⇔ raiz de 0 é 0


x'=-(-2)+0      2
   ¨¨¨¨¨¨¨¨¨¨¨¨=¨¨¨¨¨¨¨¨¨= 1
           2.1     2



x"=-(-2)-0        2                                S:(1, 1)
    ¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨¨¨ =1
       2.1          2 





c)x²-7x+12=0    onde   a=1   b=-7    c=12


Δ=b²-4.a.c
Δ=(-7)²-4.1.12
Δ=49-48
Δ=1  ⇔  raiz de 1 é 1



x'=-(-7)+1        +7+1           8
    ¨¨¨¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨¨¨¨¨¨¨¨=   ¨¨¨¨¨¨¨¨=  4
         2.1            2             2

                                                                                   S:(4, 3)

x"=-(-7)-1         +7-1         6
   ¨¨¨¨¨¨¨¨¨¨¨¨ =  ¨¨¨¨¨¨¨¨¨¨ =  ¨¨¨¨¨¨=  3
        2.1            2            2




d)-4x²+2x=2
  -4x²+2x-2=0      onde    a=-4       b=2      c=-2


Δ=b²-4.a.c
Δ=2²-4.(-4).(-2)
Δ=4-32
Δ=-28   ⇔ não possui raiz real.






Espero ter ajudado!
1 5 1